MENINGKATKAN SEMANGAT WIRAUSAHA GUNA MENGURANGI TINGKAT PENGANGGURAN DI KOTA SURABAYA - Tranggono Tranggono; Putri Rahma Sari; Azarya Rose Mariel Telaumbanua; Dioni Octaviano; Bima Sena Duanda Purwantoro; Happy Faradita; Ramadhan Irsyadi (Gapenas Publisher, 2023)
The high unemployment rate in the city of Surabaya can be overcome by increasing the entrepreneurial spirit of the community. This study aims to find out how big the entrepreneurial spirit of the people of Surabaya is and what factors influence their entrepreneurial spirit. The results of the study show that the entrepreneurial spirit of the people of Surabaya is still low, but factors such as support from the government and the community, access to resources, and entrepreneurship training can increase the entrepreneurial spirit. In this study aims to determine the importance of increasing the entrepreneurial spirit in reducing unemployment rates in the city of Surabaya. The next goal is to find out what factors influence the entrepreneurial spirit of the people of Surabaya. And in this study, it also contains goals related to solutions or recommendations to increase the entrepreneurial spirit of the people of Surabaya. As a support for this research, a quantitative method was used with a descriptive research approach by collecting questionnaire data and documentation methods distributed among the people of Surabaya. So that the data obtained shows that the entrepreneurial spirit in the city of Surabaya is in the Good category